Microscopic colitis: a descriptive clinical cohort study of 795 patients with collagenous and lymphocytic colitis. (3rd May 2016) - Mellander, Marie-Rose; Ekbom, Anders; Hultcrantz, Rolf; Löfberg, Robert; Öst, Åke; Björk, Jan
Abstract: Objective Microscopic colitis is a common cause of chronic diarrhoea in the Scandinavian countries. This report comprises demographic data, clinical and endoscopic features, and occurrence of coeliac and inflammatory bowel disease (IBD) in a large urban cohort of patients with lymphocytic colitis (LC) and collagenous colitis (CC).Materials and methods A total of 795 patients with microscopic colitis from two hospitals in Stockholm were included. Medical records were reviewed and clinical data, including endoscopic and histological findings, were compiled.Results Forty-three percent had CC (female:male ratio 3.7:1) and 57% had LC (female:male ratio 2.7:1). The mean age at diagnosis of CC was 63 years and of LC was 59 years ( p  = 0.005). Clinical features were similar in both entities, but the intensity of symptoms differed. Watery diarrhoea was reported in 55% in CC patients versus in 43% in LC patients ( p  = 0.0014), and nocturnal diarrhoea in 28% versus 18% ( p  = 0.002). Subtle endoscopic mucosal findings were reported in 37% of the CC patients and in 25% of the LC patients ( p  = 0.0011). Colorectal adenomatous polyps were found in 5.3% of all patients. Coeliac disease occurred in 6% and IBD occurred in 2.1% of all patients.Conclusions Clinical features of LC and CC are similar but not identical. CC seems to be a more severe type of bowel inflammation and LC tends to occur earlier in life. Both forms might indeed feature endoscopic findings despite the designation 'microscopic'. Our study confirms the strong association with coeliac disease.